Intensive Care Nurse Work Wellbeing: A Mixed Methods Study - Jarden, Rebecca Jane (Auckland University of Technology, 2019)
Intensive care nursing is a professionally challenging role. This is elucidated in the body of research focusing on nurses’ illbeing, including aspects such as burnout, stress, moral distress, and compassion fatigue. In contrast, little is currently known about intensive care nurse work wellbeing. The objectives of this programme of research were to conceptualise intensive care nurse wellbeing by identifying intensive care nurses’ perspectives of work wellbeing and strategies that strengthen their work wellbeing. In a two-stage mixed methods approach firstly, the existing evidence base was explored through text analytics and a systematic review. Secondly, intensive care nurses’ perspectives were sought in an online prototype analysis and a descriptive exploratory study. In stage one, a text analytics model was developed and applied to explore the size and impact, disciplinary reach, and semantics of the online publications investigating wellbeing generally, and intensive care nurse wellbeing. The intensive care nurse wellbeing literature was then systematically reviewed in an electronic search. In stage two, the prototype analysis sought intensive care nurse’s perceptions of the characteristics of their work wellbeing and explored the internal structure of the construct of work wellbeing. Finally, in a descriptive exploratory study, using free text responses, intensive care nurses reported strategies strengthening their work wellbeing. These mixed methods were then synthesised to develop a framework to support organisational change. The text analysis and systematic review identified that conceptions of illbeing were strongly represented and intensive care nurse wellbeing was virtually absent. Four primary research studies were identified in the systematic review, focusing on intensive care nurse spiritual wellbeing, team commitment, emotional wellbeing, and the effects of a mindfulness programme. The studies were heterogeneous, and of variable quality and generalisability. The prototype analysis found the terms ‘support’, ‘work-life balance’, and ‘workload’ were in the top five most frequently endorsed and rated in the top 12 most central to their conception of work wellbeing. The nurses identified personal work wellbeing strengtheners such as mindfulness and yoga. Both relational (i.e., between nurses and colleagues) and organisational strengtheners were also evident, including aspects such as peer supervision, formal debriefing, and working as a team to support each other. Work wellbeing was found to be best described as a collection of elements; a multifaceted construct. Strengtheners of intensive care nurses’ work wellbeing extended across individual, relational, and organisational resources. Actions such as simplifying their lives, giving and receiving team support, and accessing employee assistance programmes were just a few of the intensive care nurses’ identified strengtheners. The findings of this programme of research were synthesised into a framework for job crafting and redesign. This synthesis informs future strategic work wellbeing programmes, creating opportunities for positive change.
Keywords: Bibliometrics; Critical care nurses; ICU; Prototype analysis; Systematic review; Text analytics; Text mapping; Wellbeing; Work wellbeing.